The Zealandia continent: a worthy replacement for Pacifica? - Hodder, Peter (New Zealand Science Review, 2017)
​Citation analysis for papers suggesting a laterally dispersed continent (‘Pacifica’) and a submerged continent in the region of New Caledonia and New Zealand indicates sustained preference for the latter, certainly on geological evidence and probably on biogeographic evidence. However, the name assigned by geologists to this entity – ‘Zealandia’ – is historically inaccurate and politically contentious. A politically acceptable name for the continent that does not kindle post-colonial dissent might be ‘Vallardia’, reflecting the sixteenth century Portuguese maps of the region, but is unlikely to find favour with historians. A solution to this conundrum is to revive the name ‘Pacifica’.